(untitled) (Revista de Ciências Agroveterinárias, 2025)
The use of hardening or acclimatization processes in woody species seedlings has shown contradictory results in post-planting mortality. The hardening or acclimatization of woody species seedlings via mechanical treatment has resulted in differentiated nutritional allocation among plant tissues. The objective of this study was to test the effect of daily stem bending frequencies (zero, 10, 20, or 40 bends) on macronutrient allocation in Guazuma ulmifolia seedlings, using a randomized block design with five replicates of seven seedlings. The treatments tested did not show evidence of stress induction in seedlings when measured by the electrolyte leakage test in root tissues, but increased calcium and magnesium levels in the stem. The use of 10 daily stem bends resulted in an increase in nitrogen concentration in stem tissues, while phosphorus concentration increased in both the stem and roots. The imposition of 10 or 20 daily stem bends resulted in a reduction in potassium concentration in the roots, as well as an increase in calcium and magnesium levels in the stem. Due to the pioneering nature of the species and its ability to acclimatize mechanically, hardened mutamba seedlings with stem bends deserve to be tested in revegetation projects.